Implementasi pembelajaran moderasi beragama dalam membangun harmoni keagamaan di min 1 kota madiun - Maftuh Arbia Tauhid; Rosyida Nurul Anwar; Bismo Handono Warih; Ilham Mulya Pambudi; Imam Sukatno Putra; Juanda Maulana Abiyasa (Universitas PGRI Madiun, 2026)
The diversity of religious practices within the Muslim community is a reality encountered in educational environments, including at the elementary school level. Therefore, learning religious moderation is an important strategy in building internal harmony among Muslims from an early age. This study aims to describe the implementation of religious moderation learning, identify the values developed, and analyze the supporting factors and challenges of its implementation at MIN 1 Madiun City. The study used a qualitative approach with a case study type. Data were obtained through observation, interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña model through the stages of data condensation, data presentation, and concluding. Data validity was carried out through source triangulation and technical triangulation. The results of the study indicate that the implementation of religious moderation learning is carried out through inclusive learning, introduction of the concept of *khilafiyah*, habituation of tolerance, deliberation, respect for tradition, and strengthening a harmonious school culture. The leadership of the madrasah principal, teacher competence, and a conducive school culture support successful implementation. However, limited teaching materials and family influences pose challenges and hamper implementation. The implications of this research indicate that religious moderation learning can be an effective strategy for developing moderate, tolerant student character and fostering internal harmony within the Muslim community. It also serves as a good practice that other elementary schools and madrasahs can adapt.